EFEKTIVITAS MODEL PROJECT BASED LEARNING (PJBL) BERBANTUAN CANVA UNTUK MENINGKATKAN KEMAMPUAN MENULIS CERPEN PADA SISWA SMP KELAS IX - Anisa Nuraini; Teti Sobari; Indra Permana (Parole : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2026)
This article describes the results of research on the use of the Project Based Learning model assisted by Canva. This research is motivated by the low ability to write short stories, this is due to the difficulty in finding ideas, the lack of interest of students in learning short stories in grade IX students. The use of technology is rarely used in the learning process, based on this, there needs to be an update in the media used in order to create effective learning. The learning model used is not innovative, making learning outcomes less than optimal. The purpose of this study was to determine the use of the project based learning model assisted by Canva on the ability to write short story texts in grade IX students. The study used a quantitative approach and a joint testing method with a one-group pretest-posttest design. The findings of the study indicated that the average pretest score was 64.13, in contrast to the posttest score of 84.67. The findings of the study indicated that the sig value was below 0.05, which was at the Ha acceptance level (0.000 ˂ 0.05). Therefore, Ha was accepted and Ho was rejected. According to the N-Gain test, the score obtained was 0.5731, which is in the moderate category. Thus, the Problem Project Based Learning model assisted by Canva is considered effective in increasing the level of learning outcomes in writing short story texts.